Active Tectonics of the Garsela Fault Utilizing Morphotectonics and Seismicity in Garut Regency, Indonesia - Pristiwantoro, Rafa Nurul Zahra; Fahrudin; Widiarso, Dian Agus; Moechtar, Rio Alcanadre Tanjung; Cita, Akbar (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Tectonic activity along active faults in Indonesia has a high potential to cause earthquakes with magnitudes greater than 6.5. This research focuses on the Garsela Fault in Garut Regency, West Java, which has a history of shallow earthquakes occuring near nationally important infrastructure. Morphotectonic analysis, Maximum Credible Earthquake (MCE) calculations, geological structure measurements, and subsurface condition assessments were conducted to determine the tectonic activity around the Garsela Fault and its fault mechanism. The analysis results show that tectonic activity in Garut Regency ranges from low to high. The Garsela Fault is divided into two segments with different fault systems: the Rakutai Segment, a normal fault (16.22 km), and the Kencana Segment, a strike-slip fault (17.33 km). MCE calculations for the Garsela Fault indicate potential maximum magnitudes of 5.42, 5.54, 6.28, and 6.54. Shallow earthquakes may produce stronger tremors in the western part of the Rakutai Segment compared to the east. In addition, earthquakes originating from the Kencana Segment may also generate tremors in the southern part of Garut Regency.